Nepal-India Relationship: Political, Economic, and Strategic Dimensions - Kharel, Aswasthama Bhakta (Journal of Development Review, 2024)
Nepal and India share long historical, social, cultural and economic ties. Relation between two countries is significant. This research examines the multifaceted relationship between Nepal and India, focusing on the political, economic, and strategic dimensions that define their interactions. It provides a comprehensive analysis of how these dimensions influence bilateral relations, shaping regional stability and development. Using a mixed-methods approach, this research integrates qualitative analysis of historical documents, treaties, and diplomatic exchanges with quantitative analysis of trade data and economic indicators. Key political variables include diplomatic engagements, treaty agreements, and sovereignty issues, while economic variables encompass trade volumes, investment flows, and foreign aid. Strategic variables focus on military cooperation, border security, and geopolitical alliances. The findings reveal that while historical ties and economic interdependence foster a strong bilateral relationship, political disputes and strategic concerns often pose challenges. The study emphasizes that enhancing mutual trust through continuous diplomatic dialogue and collaborative development projects can mitigate conflicts and promote a more stable and prosperous partnership between the two countries. The research also contributes to the understanding of South Asian geopolitics.